Tropical forcing and ENSO dominate Holocene climates in South Africa's southern Cape - (:unkn) unknown (My University, 2024)
This paper explores the Holocene climatic dynamics of South Africa’s southern Cape, a region that supports alarge proportion of the Greater Cape Floristic Region and contains an array of important archaeological sites.While South African climates are generally characterised by marked rainfall seasonality, the southern Cape iscurrently situated at the interface between tropical and temperate climate systems, resulting in a largely aseasonalrainfall regime. This regime, however, is thought to have been particularly sensitive to past changes in lateQuaternary boundary conditions, meaning that variability in either tropical or temperate systems could havesignificant environmental impacts. Evidence of past climate change, however, remains limited.We present a 9000-year record of hydroclimatic variability obtained from rock hyrax midden stable nitrogenrecords, from Papkuilsfontein, on the southern slope of the Anysberg Mountains. Resolved to an average 6-yearresolution and spanning the period c. 9050 cal yr BP to 1990 CE, this is the highest resolution Holocene recordfrom southern Africa and presents a unique opportunity for the detailed study of the primary drivers and spatialgradients of Holocene climate change in the southern Cape. The data indicate a long-term decrease in aridityacross the Holocene and a pattern of variability that reveals remarkable similarities with records from the SouthAfrican tropics and El Ni˜no–Southern Oscillation proxies, highlighting the significance of tropical systems asdrivers of Holocene climate change in the region. This substantially expands what has been previously consideredto be the zone of tropical influence, extending from a coastal phenomenon associated with heat transport viathe Agulhas Current to encompass much, if not all, of the Agulhas Plain south of the Cape Fold Mountains. Thesefindings provide a valuable new climatic framework for contextualizing changes in ecological and archaeologicalrecords in the so
Keywords: African Research